Everyday life and postmodernism: the ethics of social life in Ágnes Heller - Portanova Barros, Eduardo; César Santos Fonseca, Antônio (Latitude, 2024)
This article is inspired by the reflections of the Hungarian philosopher Ágnes Heller (representative of the so-called Budapest School), especially in two of her works: “Políticas de la postmodernidad” (1989), co-authored with Ferenc Féher, and “The Daily Life and History”, originally written in 1970. We are not interested here in his debt to Marxist thought, from which his work, a disciple that he was of George Lukács, originates, but rather the circumstances of complex human relations as a dialectic between life and everyday life. It is concluded that the heterogeneous aspect of which Heller speaks to us, without any universal hierarchy (in her words), is an affirmation (without labeling or absolutisms) of the postmodern theories of “decentralization of the subject” (Hall), “weak thinking” (Vattimo) or “elective affinities” (Maffesoli), among other theorists of this hermeneutic-phenomenological approach.